Tongue thrusting habit and its treatment: Kebiasaan menjulurkan lidah dan penanganannya - Baharuddin M. Ranggang; Meiky Eka Saputra (Makassar Dental Journal, 2026)
Tongue thrusting is the habit of protruding the tongue and pressing against the front teeth at rest, while speaking, or swallowing, which can lead to malocclu-sion. To overcome this habit, devices such as removable or fixed tongue cribs can be used. The habit of protruding the tongue causes an imbalance in the muscles of the mouth, which ultimately results in malocclusion, namely the incisors being pushed forward and an open bite. To overcome the habit of protru-ding the tongue, speech therapy, myofunctional therapy, tongue exercises, and the use of orthodontic appliances such as removable or fixed tongue cribs can be used. Variations of the tongue crib include the hybrid habit-correcting appliance, tongue crib with cold-cure acrylic, tongue shield, fixed palatal crib with trans-palatal arch, fixed tongue loops, tongue fence, and upper hay rake. It is concluded that the habit of protruding the tongue can be addressed using a remova-vable or fixed tongue crib.